Sosialisasi Akreditasi Rumah Sakit Berdasarkan Elemen Penilaian MRMIK 3 LAM-KPRS di RSIA Mutiara Bunda - Dewi Oktavia; Sayati Mandia; Marsya Dwi Ananta (Joong-Ki : Jurnal Pengabdian Masyarakat, 2025)
Hospital accreditation is the process of assessing healthcare standards to improve patient quality and safety. One important aspect of accreditation is medical records management, which encompasses the effective storage, management, and utilization of data and information. Bunda Ibu Anak Hospital, Padang, as a hospital focused on maternal and child health services, has specific needs when implementing a medical records management system. The patient data managed at this hospital encompasses not only general medical records but also information related to pregnancy, childbirth, and neonatal care, which require more detailed and accurate recording. Therefore, this hospital needs to implement a document management system that all policies and procedures used are in accordance with standards. This PKM aims to provide understanding to medical record officers regarding the implementation of the Medical Record Management System at Ibu Anak Bunda Hospital Padang based on the MRMIK 3 standard. The expected benefit is to increase the level of knowledge of medical record officers regarding accreditation assessments based on MRMIK3 LAM-KPRS. This Community Service activity was carried out by providing socialization on Friday, July 4, 2025 at Mutiara Bunda Hospital. This activity was successful and ran smoothly. Suggestions from the MRMIK 3 accreditation socialization at Mutiara Bunda Hospital will be more optimal if the assessment process for health service standards is carried out continuously, strengthened by internal training and evaluation, supported by a special team and the use of an integrated SIMRS, and fostering a culture of quality throughout the hospital line